Jazz in Lampung: Community’s Perspective, Social Practices, Cultural Performance, Organization, and Consequences - Hidayatullah, Riyan; Irawan, Ricky; Alam, Pandu Watu; Mazlan, Chamil Arkhasa Nikko (Institut Seni Indonesia Yogyakarta, 2024)
This article attempts to reveal the perspectives of the Lampung jazz community members dealing with organizational issues related to members’ perceptions or administrators. The cause is an extramusical issue that leads to the ulun Lappung (indigenous Lampung people) social characteristics. In general, problems uncommon in the jazz community arise in this communal setting. This article focuses on the Lampung jazz community’s perspective, cultural performances, social practices, and consequences. The data for this study came from immersive fieldwork conducted in Lampung jazz circles between 2017 and 2021. In addition to in-person data collection, field sites and apps were used. The research participants include senior musicians with over 20 years of experience, music scholars, music entrepreneurs, and jazz activists. Each participant has a unique perspective on group organization, jazz culture and knowledge, and socially musical practices. The significance of Lampung’s musical sense of community is discussed.